2011
DOI: 10.1128/aem.02405-10
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Island Markers, Virulence Determinants malX and usp , and the Capacity of Escherichia coli To Persist in Infants' Commensal Microbiotas

Abstract: Virulence-associated genes in bacteria are often located on chromosomal regions, termed pathogenicity islands (PAIs). Several PAIs are found in Escherichia coli strains that cause extraintestinal infections, but their role in commensal bowel colonization is unknown. Resident strains are enriched in adhesins (P fimbriae and type 1 fimbriae), capsular antigens (K1 and K5), hemolysin, and aerobactin and mostly belong to phylogenetic group B2. Here, we investigated whether six pathogenicity islands and the virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 50 publications
10
72
0
Order By: Relevance
“…1). These data support the notion that extraintestinal virulence may be a by-product of commensalism: numerous "extraintestinal virulence genes" (coding for adhesins, iron capture systems, toxins, and protectins) exhibited by phylogroup B2 strains (6,46) may have evolved primarily to allow the bacteria to be good intestinal colonizers (24,28,(47)(48)(49). When phylogroup B2 is dominant, it does not cooccur with the residence of other phylogroup strains, possibly due to higher fitness (50,51).…”
Section: Discussionsupporting
confidence: 65%
“…1). These data support the notion that extraintestinal virulence may be a by-product of commensalism: numerous "extraintestinal virulence genes" (coding for adhesins, iron capture systems, toxins, and protectins) exhibited by phylogroup B2 strains (6,46) may have evolved primarily to allow the bacteria to be good intestinal colonizers (24,28,(47)(48)(49). When phylogroup B2 is dominant, it does not cooccur with the residence of other phylogroup strains, possibly due to higher fitness (50,51).…”
Section: Discussionsupporting
confidence: 65%
“…The iut gene was common in 6/7 strains, and was always associated with other VFs. Moreover, the presence of some virulence genes, such as hh/A, cnfl, fimA,fyuA and malX, suggests the presence of PAIs 24 , 26 in all E. coli strains tested, except in one isolate (cat 3). Five CTX-M-type E. coli strains contained class 1 inte-grons; however, the gene cassettes aadA and dfrAl+aadA (conferring resistance to trimethoprim and streptomy-cin-spectinomycin, respectively) were found in only two isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that compared the levels of ExPEC and IPEC VGs in isolates recovered from stool samples of healthy humans found Ͼ31% and Ͻ5% of these isolates to carry ExPEC and IPEC VGs, respectively (10,53). Studies of specific clones showed that dominant or resident clones have more ExPEC VGs than minor or transient ones (54)(55)(56)(57). Finally, a study using E. coli strain 536 (UPEC) in which the seven PAIs had been deleted showed that the wild-type strain had a marked advantage for intestinal colonization in a mouse model, while the PAI-deleted mutant had a competitive advantage in laboratory batch cultures (58).…”
Section: Discussionmentioning
confidence: 99%